Management of Geographic Tongue in a Patient with Mango Alergy Accompanied with Fissure Tongue, Oral Candidiasis and Cheilitis - Sri Hernawati (Humanistic Network for Science and Technology (HNST), 2019)
The tongue is a solid organ formed by skeletal muscles that has an important function as the sense of taste, mastication, swallowing, and speaking. There are several physiological conditions on the tongue which can be pathological conditions e.g. Geographic tongue and Fissured tongue. This situation may occur due to trigger factors e.g. allergic reactions. Allergies of certain fruits e.g. mangoes are very rare. However, in some patients those cases may cause immediate or delayed hypersensitivity reactions. A 40-year-old male patient complained that his tongue felt sore after eating a lot of mango salad, after clinical examination the results showed clinical appearance were: 1) island-shaped atrophy, surrounded by white edges, pain; 2) fissure, multiple, redness, pain; 3) yellowish white plaque, can be scraped, no clear boundary, no pain in the dorsum of the tongue. In addition to the extraoral examination there were abnormalities in the upper and lower lips of the patient in the form of fissure, vertical, multiple, accompanied by desquamation. The final diagnosis the patient was geographic tongue with fissured tongue, oral candidiasis in the dorsum of the tongue, and cheilitis on the upper and lower lips. Therapy provided to patient was topical benzidamine HCl oral oral anti-inflammatory medicine, oral suspension topical nystatin antifungal, OM ointment, Becomzet multivitamin (Vitamin B complex, A, C, E, and Zinc) as multivitamin and tongue cleaner. Two weeks after treatment with benzydamine HCL which acts to inhibit TNFα and prostaglandin, administration of ointments that are analgesic and help the healing process (for geographic tongue and fissure tongue), and administration of nystatin for oral candidiasis, nystatin a macrolide polyene whose toxicity low and specific for candida albicans, accompanied by multivitamins that help the healing process, tongue geography, tongue fissure and oral candidiasis heal. Keywords: fissure tongue; oral candidiasis; cheilitis; mango